Microwave hybrid heating of materials using susceptors- a brief review - Yahaya, B.; Izman, S.; Konneh, Mohamed; Redzuan, Norizah (Trans Tech Publications, Switzerland, 2014)
This article discusses the fundamentals and benefits of microwave hybrid heating. High dielectric loss materials can be processed using direct microwave heating, whereas low dielectric loss materials can only be process using microwave through microwave hybrid heating. It was shown that it is possible to virtually process any type of materials via microwave hybrid heating. Microwave hybrid heating offers faster heating rate than direct microwave heating. It reduces the problem of thermal runaway experience in direct microwave heating of high dielectric loss materials. The two basic types of microwave hybrid heating techniques were discussed with emphasis on the use of susceptor. Microwave hybrid heating using susceptor offers the advantage of using single energy source.